Association between Genetic Polymorphisms in Interleukin Genes and Recurrent Pregnancy Loss - A Systematic Review and Meta-Analysis. - Meixiang Zhang; Jiawei Xu; Xiao Bao; Wenbin Niu; Linlin Wang; Linqing Du; Nan Zhang; Yingpu Sun (PLoS ONE, 2017)
Interleukins are a group of immunomodulatory proteins that mediate a variety of immune reactions in the human body. To investigate the association between interleukin gene polymorphisms and recurrent pregnancy loss (RPL), we reviewed 21 studies from MEDLINE, EMBASE, OVID SP and PubMed to evaluate RPL-related interleukin gene polymorphisms. Meta-analysis was performed on 12 of the polymorphisms, and a review included the others. Our integrated results indicated that IL-1β (-511C/T) (P = 0.02, 95% CI 0.77[0.62,0.96]), IL-6 (-634C/G) (P<0.001, 95% CI 2.91[2.01,4.22]), IL-10 (-1082G/A, -819T/C) (P = 0.01, 95% CI 0.80[0.67,0.96]; P<0.01, 95% CI 0.66[0.49,0.89]), and IL-18 (-137G/C, -105G/A) (P<0.01, 95% CI 1.69[1.24,2.31]; P = <0.01, 95% CI 1.41[1.17,1.70]) consistently associated with RPL after meta-analysis. IL-17A rs2275913 and IL-17F rs763780, IL-21 rs2055979 and rs13143866, IL-1β (-31C/T), IL-6 (-2954G/C), and IL-10 (-536A/G) were reported only once as having a significant association with RPL. The potential mechanism underlying miscarriage and these polymorphisms and future research directions are also discussed.